The effect of particle compositions on the activation energy of the pa6/bagasse composite. (August 2019) - Thalib, S; Huzni, S; Fonna, S; Azhari, C H; Zakaria, S
Abstract: The Activation energy of PA6/Bagasse particles blends was evaluated as a function of particle compositions. The composite was prepared in compositions of weight %PA 6%/weight Bagasse particles, that is 95/5, 90/10 and 87.5/12.5 respectively using a twin screw extruder at 40 rpm and 220 °C blending temperature. The Activation energy is determined based on rheological testing with using a capillary rheometer on constant heating method. In this test, it is obtained the relationship of viscosity and temperature of melting composite. Arrhenius linear plot between viscosity to 1/T. can be obtained the activation energy.